William Kraft’s Concerto No. 1, and Michael Daughtery’s Raise the Roof: a pedagogical and historical study of contemporary timpani concerti - Fleischmann, Houston (My University, 2025)
This report presents an examination of the historical, pedagogical, and musical significance of two contemporary timpani concerti: William Kraft’s Concerto for Timpani and Orchestra, No. 1, and Michael Daugherty’s Raise the Roof. By researching the composers and observing the compositional advancements written for timpani by each composer, the study explores how both composers have contributed to the advancement of timpani as a solo instrument and the expansion of the timpani repertoire in the 20th and 21st centuries. The research investigates the stylistic and technical demands of each concerti, its historical genesis, and its role in modern timpani pedagogy. Through a detailed examination of the timpani parts, performance practices, and the author’s individual notes from preparing Raise the Roof, this report aims to provide a comprehensive understanding of these works, highlighting their relevance in both academic and professional settings. The study also offers insights into how contemporary timpani concerti challenge traditional playing techniques, while offering pedagogical tools for the development of future timpani performers.
Keywords: Music; Timpani; Concerto